COMMUNICATION STRATEGIES FORMATION OF MODERN UNIVERSITY - Ilhanaieva, Valentina (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
Research is devoted to consideration of modern university as a part of social communication area of society and analysis of its external and internal features of communication activity.